Penyelesaian Tindak Pidana Pengerusakan Melalui Pendekatan Restorative Justice - Pranata, Akhmad Indra; Indrawan, Rudy (Fakultas Syariah IAI Muhammadiyah Bima, 2025)
This article explores the resolution of the criminal act of vandalism through a restorative justice approach. Under Indonesian criminal law, vandalism is regulated in Article 406 of the Criminal Code with a maximum prison sentence of two years and eight months. However, the retributive approach is considered less effective in achieving substantive justice as it focuses solely on punishing the offender. This study employs a normative legal method with statutory, conceptual, and comparative approaches to examine the urgency of implementing restorative justice in resolving vandalism cases. The findings indicate that restorative justice offers a more humane approach by prioritizing the restoration of relationships between offenders and victims through mediation and mutual agreement. This approach aligns with local cultural values such as deliberation and contributes to reducing the burden on judicial and correctional institutions. Moreover, restorative justice provides a fairer and more efficient resolution, strengthening community involvement in legal enforcement. Therefore, this approach is relevant for application in vandalism cases that meet the established criteria, as a means to achieve balanced justice and restore the condition of all parties involved. Keywords: restorative justice, vandalism, restoration, alternative sentencing, criminal law